Academic achievement among a sample of youth in foster care: The role of school connectedness. Issue 12 (14th August 2020) - Somers, Cheryl L.; Goutman, Rachel L.; Day, Angelique; Enright, Oliva; Crosby, Shantel; Taussig, Heather
Abstract: Research shows that youth in foster care experience poor academic performance and disciplinary actions in school more frequently than do non‐foster care youth. The purpose of this cross‐sectional study was to further examine youth in foster care and the relationship between individual/intrapersonal factors (future orientation and school connectedness) and exosystem factors (number of placement and school moves) and academic performance (grades) and disciplinary referrals among 363 youth (9–11 years of age; males = 52.9%). Controlling for key variables, hierarchical linear regression analysis was utilized to understand how well students' school connectedness, future outlook, number of placement changes, and number of school moves predicted academic and disciplinary outcomes. Beyond the variance explained by control variables, school connectedness made a significant contribution to this model. Results are discussed in the context of implementing interventions that foster school connectedness among this vulnerable population.